Conciencia ambiental en estudiantes de 5to grado nivel secundario en instituciones educativas rural y urbana de la provincia de Maynas. año 2023 - Torres Marin, Marco Antonio (2024)
The study was carried out in the city of Iquitos, the design was descriptive, analytical and transversal; with the purpose of evaluating and comparing the level of environmental awareness of students in the 5th year of the secondary level of the rural IE 60115 MIGUEL GRAU SEMINARIO of Padre Cocha, district of Punchana; and the urban IE 60188 SIMÓN BOLÍVAR, district of Iquitos. The population was made up of all 5th year students from both educational institutions and the sample size is 46 students from the rural IE and 94 students from the urban IE, the data were collected through a structured survey-type questionnaire, which consists of 2 parts, the first cognitive with 11 questions and the second behavioral on the Likert scale with an instrument reliability of 0.733 of the Cronbach's Alpha coefficient, for the statistical analysis the Pearson Correlation Coefficient was used and which allowed us to conclude: The students Both schools have a high level of environmental knowledge, but the students from the urban school have slightly higher knowledge than the students from the rural school, in relation to environmental behavior. The students from both schools present a high level, but the students from the rural IE have a slightly higher behavior than the urban school and that would be related to a daily practical connection of the students with the activities in their environment. In relation to environmental awareness, students from the urban school show a high level of environmental awareness, slightly higher than the rural school. According to Pearson's r test, the null hypothesis is rejected and the alternative hypothesis is accepted: that is, there is a significant difference in environmental awareness related to knowledge (cognitive) and behavior (behavioral) in 5th grade secondary school students. rural versus urban environment.